AUTOMATION OF MANAGEMENT BY THE INTELLECTUAL THE RIGHTS IN GLOBAL COMPUTER NETWORKS - Anatoly P. Yakimaho; Victoriya V. Bessarabova (Статистика и экономика, 2016)
In article authors analyze problems of useof objects of intellectual property in globalcomputer networks. The main attentionis concentrated on effective ways of thesolution of the problems arising for users.The special attention is paid to questionsof creation of system of automatic controlby property rights of authors and owners inglobal computer networks.